2012
DOI: 10.1155/2012/306530
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Nutrient Intake and Nutrient Status of HIV Seropositive Patients Attending Clinic at Chulaimbo Sub-District Hospital, Kenya

Abstract: Background. Nutritional status is an important determinant of HIV outcomes. Objective. To assess the nutrient intake and nutrient status of HIV seropositive patients attending an AIDS outpatient clinic, to improve the nutritional management of HIV-infected patients. Design. Prospective cohort study. Setting. Comprehensive care clinic in Chulaimbo Sub-District Hospital, Kenya. Subjects. 497 HIV sero-positive adults attending the clinic. Main Outcome Measures. Evaluation of nutrient intake using 24-hour recall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
3
12
2
Order By: Relevance
“…Studies have indicated lower nutrient intakes for Zinc, Calcium and Iron among women than males and this may be attributed to consumption of low intakes which are deficient of nutrients. 36 , 37 On the other hand, Uganda’s household diet is predominantly vegetable and tubers. 4 , 37 The fact that males have a higher chance of consuming foods away from home, may increase chances of consuming a variety of foods than women who mostly depend on home prepared meals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated lower nutrient intakes for Zinc, Calcium and Iron among women than males and this may be attributed to consumption of low intakes which are deficient of nutrients. 36 , 37 On the other hand, Uganda’s household diet is predominantly vegetable and tubers. 4 , 37 The fact that males have a higher chance of consuming foods away from home, may increase chances of consuming a variety of foods than women who mostly depend on home prepared meals.…”
Section: Discussionmentioning
confidence: 99%
“…The effects are interrelated and exacerbate one another in a vicious cycle [5]. Both HIV and malnutrition can independently cause progressive damage to the immune system and increased susceptibility to infection, morbidity, and mortality through opportunistic infections, fever, diarrhea, loss of appetite, nutrient absorption, and weight loss.…”
Section: Advances In Public Healthmentioning
confidence: 99%
“…The selection of participants was random as they came to the Laboratory of the hospital to carry out other Laboratory investigations, and it is after the selection that the participants were separated into two groups. Diet variety was assessed using a food frequency checklist and nutrient intake using 24-hours dietary recall 9 . We also recorded the amount of physical activity/week and this is because of the correlation between physical exercise and diabetes mellitus.…”
Section: Methodsmentioning
confidence: 99%